Factors Influencing Online Learning Students’ Satisfaction in UIN Fatmawati Bengkulu - Eko Ngabdul Shodikin; Agung Rokhimawan; Ahmad Suradi; Setia Murningsih (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The use of e-learning in education can increase efficiency and motivation in learning. The success of this online learning platform is influenced by student satisfaction. Students who are satisfied then they will be comfortable with using online learning. The success of the online learning system can be seen in student satisfaction when using the LMS and online learning software. So, this study aims to analyse student satisfaction with the online learning system. The sample of this research is students of the Tarbiyah Faculty of UIN Sukarno Fatmawati Bengkulu. The sampling technique used is convenience sampling. The independent variables used were computer self-efficacy (CSE), perceived usefulness (PU), and perceived ease of use (PEU). The dependent variable in this study was student satisfaction (SAT). This data analysis technique used Structural Equation Modelling (SEM) with SmartPLS software. The results of this study indicated that the computer self-efficacy had a significant positive effect on the perceived ease of use and the perceived usefulness. The perceived ease of use and perceived usefulness significantly positively affected the student’s satisfaction.  Keywords: Online Learning Higher Education, Students’ Satisfaction, Structural Equation Modeling